On the Uniqueness of Certain Type of Shift Polynomial Sharing a Small Function - Majumder Sujoy (Annals of the West University of Timisoara: Mathematics and Computer Science, 2017)
The purpose of the paper is to study the uniqueness problems of certain type of difference polynomial sharing a small function. We point out and rectify some gaps in the proof of the main results in [8]. In addition to this we obtain our main result as a corrected and generalized version of [8] in a more compact way which in turn improve a number of earlier results.